Economics of Range Reseeding in Arid Western Rajasthan - Sharma, S K; Mrithyunjaya, Mrithyunjaya (Annals of Arid Zone, 2016)
Economics of range reseeding with Cenchrus ciliaris and Cencllrus setigerus strains at Jodhpur and Samdari in western Rajasthan, was worked out by method of discounting. Reseeding with C. ciliaris strain Palsana is suggested for areas similar to Jodhpur and with C. ciliaris strain 358 for areas similar to Samdari.